Multistage Solvent Extraction for High Yield Oil and Phorbol Esters Removal from Thai Toxic Jatropha curcas Meal - NOKKAEW, Rayakorn; PUNSUVON, Vittaya (Walailak Journal of Science and Technology (WJST), 2013)
In this study, we investigate the possibility for the production of high yield oil and phorbol esters removed from Thai toxic Jatropha curcas meal. Optimum oil recovery by hexane extraction to obtain high oil yield was accomplished in 3 stages of batch extraction, following which the de-oiled meal was further determined for the optimum conditions for removal of phorbol esters (PEs) by aqueous ethanol extraction from the first to the third stage of batch extraction with the aim of yielding detoxified de-oiled meal product for use as a raw material in animal feed. The optimum conditions for oil extraction was 3-stage extraction with each stage operated at 1:3 (w/v) of toxic meal to hexane at 40 °C for 30 min. This condition gave 100 % de-oiling efficiency compared with the Soxhlet extraction method. The optimum condition for PEs removal from the de-oiled meal involved 2-stage extraction with each stage operated at 1:3 (w/v) of de-oiled meal to aqueous ethanol at 50 °C for 30 min. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) in the multiple reaction monitoring mode, was used to confirm the PEs residue in the detoxified de-oiled meal. The confirmation showed that the 2 stages of PEs extraction could remove 100 % of the PEs from the de-oiled meal. The results from our study can provide the basis for the efficient commercial production of both J. curcas oil and detoxified de-oiled meal. doi:10.14456/WJST.2015.32